2020
DOI: 10.3390/cryst10070555
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Based in Situ Investigation of Silicon Growth Mechanism Dynamics—Application to Grain and Defect Formation

Abstract: To control the final grain structure and the density of structural crystalline defects in silicon (Si) ingots is still a main issue for Si used in photovoltaic solar cells. It concerns both innovative and conventional fabrication processes. Due to the dynamic essence of the phenomena and to the coupling of mechanisms at different scales, the post-mortem study of the solidified ingots gives limited results. In the past years, we developed an original system named GaTSBI for Growth at high Temperature ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
(165 reference statements)
0
3
0
Order By: Relevance
“…It is composed of a high temperature (up to 1800 • C) directional solidification (DS) furnace coupled with synchrotron radiation X-ray imaging techniques (Bragg diffraction imaging and radiography). A more detailed description of the device and of the X-ray imaging methods can be found in Ouaddah et al [9]. The Si samples (38 mm × 5.8 mm × 0.3 mm), housed in a boron nitride crucible, are introduced inside the DS furnace.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is composed of a high temperature (up to 1800 • C) directional solidification (DS) furnace coupled with synchrotron radiation X-ray imaging techniques (Bragg diffraction imaging and radiography). A more detailed description of the device and of the X-ray imaging methods can be found in Ouaddah et al [9]. The Si samples (38 mm × 5.8 mm × 0.3 mm), housed in a boron nitride crucible, are introduced inside the DS furnace.…”
Section: Methodsmentioning
confidence: 99%
“…The ultimate goal of this paper is to shed some light on this matter by drawing a comparison between experimental investigations and phase field simulations. Experimental investigations are based on directional solidification experiments of thin model samples in which the interface dynamics and generation of structural defects is characterized by in situ X-ray imaging during solidification [9].…”
Section: Introductionmentioning
confidence: 99%
“…More complex and nonlinear phenomena begin to appear in intense laser fields, among which high-order harmonic radiation [15] can most practicably be applied as an x-ray or even a γ-ray source. Twisted x-rays have great application prospects in multiple fields including modern astrophysics [16], imaging and information technology [17], and grain formation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, there is no residual stress in non-coherent GBs, 26) while a residual stress exists at CSL GBs. 17,[26][27][28][29] It is suggested that non-coherent GBs would not have significant internal energy for defect generation. 29) Those properties have been applied to design HP and SMART Si ingots with an optimum dislocation density.…”
mentioning
confidence: 99%
“…Ouaddar has reported that, no local strain is accumulated at Σ3{111} GBs except at their terminations, while a local strain is accumulated at GBs with Σ > 3 during the crystal growth; the degree of the strain would increase with increasing the Σ number. 27) According to the CSL theory, 25) when a GB is connected with a pair of Σ3 GBs, the Σ-number of the GB segment between the connected lines triples and the area nearby the segment would be distorted during the cast growth. Similarly, the vicinity of a junction of GBs would be distorted, due to their low symmetry and non-coherency, as observed in a junction of CSL GBs.…”
mentioning
confidence: 99%